Determination of the optimal chemotherapy drugs pretreatment time through cultivation of hemopoietic cells in CML-patients treated with tyrosine kinase inhibitors - Zhaleiko, I.O.; Perekhrestenko, T.P.; Bilko, D.I.; Dyagil, I.S.; Bilko, N.M. (Experimental Oncology, 2014)
Background: Targeted therapy drugs, including imatinib, are used for inhibiting the marker oncoprotein of chronic myeloid leukemia — BCR-ABL tyrosine kinase. However, in some patients the drug resistance can emerge too rapidly and a previous treatment with chemotherapy drugs can lead to formation of resistance. Aim: To evaluate the influence of drugs that were used prior to the imatinib on the performance of the functional activity of bone marrow cells from chronic myeloid leukemia patients and their individual responses to therapy. Methods: Bone marrow aspirate from 57 patients, who were getting busulfan (19 patients) or hydroxycarbamide (38 patients) prior to imatinib was studied with cytogenetic and tissue culture methods in vitro. Results: Obtained data suggested that pretreatment with busulfan, regardless of duration, negatively affects the response to further therapy with imatinib. Instead, after using hydroxycarbamide as a previous therapy for six month, there was optimal response to imatinib. In those cases when duration of pretreatment with hydroxycarbamide was increased to a year or more, there was a suboptimal response and a resistance to imatinib therapy. In addition, there was a positive correlation between the number of cell aggregates (colonies and clusters) in semisolid agar and the duration of a prior treatment with hydroxycarbamide, if previous therapy did not exceed 20 months. With an increase of pretreatment terms to 21 months or more, such a correlation was not observed. Conclusions: These results suggest that chemotherapeutic agents (busulfan and hydroxycarbamide) may additionally contribute to the accumulation of mutations in the genome of leukemic cell clone affecting the behavior of these cells in vitro. Key Words: chronic myeloid leukemia, imatinib, pretreatment, hydroxycarbamide, busulfan, cell culture in vitro.